Sistem Informasi Eksekutif Fakultas Teknologi Komunikasi dan Informatika Universitas Nasional - Fendy Sulistyo; Septi Andryana; Winarsih Winarsih (STMIK Budi Darma, 2020)
Current technological developments, in the activities of information search and decision making at the Faculty of Communication and Information Technology of the National University have not been effective. Because the amount of data available makes it difficult for users to find the specific data needed. Like looking for student data based on class, religion and gender. Therefore, the Executive Information System of the Faculty of Communication and Information Technology of the National University was designed to be web-based so that users could find the required data. Application trial results to search for student data, the system can display search results by force, religion and gender with 100% accuracy. In searching the system data lecturers can display search results based on their latest education, expertise and research with 100% accuracy. Then for the data search system teachers can display search results based on the latest education and expertise with 100% accuracy. The system can also display the number of students by force, the number of lecturers based on expertise and the number of education personnel based on recent education in graphical form